2023
DOI: 10.3390/ijerph20010800
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Depression and Anxiety among Young Rural and Urban Australians: A Systematic Review and Meta-Analysis

Abstract: Globally, depression and anxiety are major public health concerns with onset during adolescence. While rural Australia experiences overall lower health outcomes, variation in mental health prevalence rates between rural and urban Australia is unclear. The aim of this paper was to estimate the pooled prevalence rates for depression and anxiety among young Australians aged between 10 and 24 years. Selected studies from a systematic literature search were assessed for risk of bias. Random effects model using DerS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 69 publications
1
10
0
1
Order By: Relevance
“…A recent systematic review including more than 7000 Australian youth aged between 10 and 24 reported that depression and anxiety were more prevalent in urban than rural areas. However, the difference was not statistically significant 37 . Community belongingness may lead to better mental health status in rural adolescents 37 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent systematic review including more than 7000 Australian youth aged between 10 and 24 reported that depression and anxiety were more prevalent in urban than rural areas. However, the difference was not statistically significant 37 . Community belongingness may lead to better mental health status in rural adolescents 37 .…”
Section: Discussionmentioning
confidence: 95%
“…However, the difference was not statistically significant. 37 Community belongingness may lead to better mental health status in rural adolescents. 37 Therefore, monitoring this behavior, specially in urban adolescents, seems relevant to avoid possible future mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review study that was conducted using 10 studies in Australia and on 7650 participants between 10 and 24 years of age showed a 21.3% prevalence of depression in this country. 1 Another study in China showed that 13.06% of primary and high school students experienced depressive symptoms. 67 The prevalence of depression signs among adolescents T A B L E 1 Included studies in the current systematic review and meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the prevalence of depression in Iranian children and adolescents was 33.4%. A systematic review study that was conducted using 10 studies in Australia and on 7650 participants between 10 and 24 years of age showed a 21.3% prevalence of depression in this country 1 . Another study in China showed that 13.06% of primary and high school students experienced depressive symptoms 67 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation